Tumor mutation burden to tumor burden ratio and prediction of clinical benefit of anti-PD-1/PD-L1 immunotherapy. (July 2018) - Qin, Bao-Dong; Jiao, Xiao-Dong; Zang, Yuan-Sheng
Abstract: Immune checkpoint inhibitors have profoundly altered the therapeutic landscape of several malignancies. The establishment of predictive biomarkers for checkpoint blockades is of the considerable importance in the identification of populations likely to experience a good response to immunotherapy and to maximize the therapeutic benefits. Several trials showed that the tumor mutation burden (TMB) could predict the response to immunotherapy, but some lower clinical benefit was also seen in cancer with high TMB. The imbalance between the strength of immune response and pretreatment tumor burden (TB) could also cause immunotherapy to fail in cancer patients. For this reason, we hypothesized that the TMB-TB ratio could predict the clinical benefit of checkpoint inhibitor immunotherapy and that PFS or ORRs should be used more often in patients with high TMB-TB ratio than in individuals with low TMB-TB ratios.